(untitled) (Bangladesh Rice Journal, 2026)
Cold injury-induced spikelet sterility and flash flood inundation at pre-ripening to ripening stages of Boro rice are common phenomena in the haor areas of Bangladesh. The development and deployment of short-duration and cold-tolerant high-yielding rice varieties can be a sustainable solution to address these issues. This study reports the development of recombinant inbred lines (RILs) using a local cultivar, ‘Rata Boro’ collected from haor areas, as a donor for cold tolerance. The RILs were screened under cold-stress environment to identify short-duration, cold-tolerant breeding lines at the reproductive stage. A total of 398 RILs were developed from crosses between Rata Boro and three elite breeding lines, and advanced to F5 generations through single-seed descent-based rapid generation advance techniques. The first-year evaluation of 425 genotypes including 398 RILs and 27 parental lines under cold-stress conditions in the field at Gazipur during Boro 2023-24 identified 11 breeding lines with minimal reduction in yield and spikelet fertility. The subsequent multi-location testing of these selected entries in Boro 2024-25 revealed a differential adaptation pattern. Genotypes G5 (BR14628-4R-156-Gaz-1), G3 (BR14628-4R-125-Gaz), G7 (BR14628-4R-198-Gaz-1), and G9 (BR14628-4R-50-Gaz-1) exhibited superior performance and specific adaptation to cold-prone haor environments. Additionally, G6 (BR14628-4R-180-Gaz-1) and G11(BR11894-R-R-R-R-169) demonstrated broad adaptability and stability across all test sites. Notably, G3, G6, and G9 consistently produced high yields under both cold-stress and non-stress conditions. These cold-tolerant RILs represent valuable genetic resources for improving cold tolerance in rice and for future studies aimed at elucidating underlying mechanisms of cold tolerance. Bangladesh Rice J.28(2): 1-23, 2024